Blotto, Twinks and the suspicious guests - Brett, Simon (Brett, Simon. Blotto and Twinks mystery, 2022)
'What? You mean the earl does it for money? That's way beyond the barbed wire!' This explosion of disgust from Blotto is provoked when Twinks informs him of the activities of the Earl of Woking. The gentleman in question is owner of Clusters, a stately home not far from Tawcester Towers, and he has been renting out parts of Clusters for private functions - and charging his guests! The discovery of this appalling lapse in aristocratic behaviour sets Blotto and Twinks off on their latest adventure. Determined to find out more about the Earl of Woking's activities, they discover the existence of a sinister group called Aristotours - brokers between impoverished owners of stately homes and the common people, offering 'a taste of the high life' to characters such as stockbrokers, surgeons and solicitors. And if this were not bad enough, the siblings discover Aristotours trying to infiltrate their evil practises into Tawcester Towers itself! So Blotto and Twinks set off on a quest to identify - and stop - the evil genius behind Aristotours.